2014
DOI: 10.4067/s0717-92272014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Perfeccionismo e insatisfacción corporal en los trastornos de la conducta alimentaria

Abstract: Background: There is an important relationship between perfectionism (P), body dissatisfaction (BD) and eating disorders (ED). Objective: To describe the evidence about P and/or BD within the clinical course of ED. Method: A review of specialized textbooks and the available literature in PubMed was made. Two descriptive case reports are analyzed. Results: Socially prescribed and self-oriented dimensions of P were related to ED attitudes and specially restrictive behaviors, mediating and moderating the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
3
0
16
Order By: Relevance
“…The relationship of perfectionism with a higher risk of later ED development has been confirmed (López & Treasure, 2011;Pamies & Quiles, 2014). Likewise, high levels of perfectionism have been affirmed in the development of bulimic symptomatology when combined with the percep-tion of being overweight (Vohs et al, 2001), that along with perceived weight and self-esteem, can prospectively predict the development of bulimic symptoms in young women (Bardone-Cone, Abramson, Vohs, Heatherton, & Joiner, 2006), and that socially prescribed and self-oriented perfectionism is significantly associated with attitudes and behaviors compatible with ED, mainly restrictive, categorizing as a mediator and moderator of the relationship between body image and ED (Behar, Gramegna, & Arancibia, 2014;Pamies & Quiles, 2014). In addition, in studies on personality profiles of the different ED, perfectionism appears in the profile of anorexia, bulimia and binge eating disorder (Cassin & von Ranson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of perfectionism with a higher risk of later ED development has been confirmed (López & Treasure, 2011;Pamies & Quiles, 2014). Likewise, high levels of perfectionism have been affirmed in the development of bulimic symptomatology when combined with the percep-tion of being overweight (Vohs et al, 2001), that along with perceived weight and self-esteem, can prospectively predict the development of bulimic symptoms in young women (Bardone-Cone, Abramson, Vohs, Heatherton, & Joiner, 2006), and that socially prescribed and self-oriented perfectionism is significantly associated with attitudes and behaviors compatible with ED, mainly restrictive, categorizing as a mediator and moderator of the relationship between body image and ED (Behar, Gramegna, & Arancibia, 2014;Pamies & Quiles, 2014). In addition, in studies on personality profiles of the different ED, perfectionism appears in the profile of anorexia, bulimia and binge eating disorder (Cassin & von Ranson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Está descrito que la baja autoestima es una variable frecuente entre las pacientes con ANR (Asuero et al, 2012;Behar et al, 2014;Cervera et al, 2003;Dunkley y Grilo, 2007;Sassaroli y Ruggiero,…”
Section: Discussionunclassified
“…Thus, this pathology appears to alter the stabilization of the voice tone. 4) It is known that patients who suffer from AN-R usually have a low self-esteem (Asuero, Avargues, Martin y Borda, 2012;Behar, Gramegna y Arancibia, 2014;Cervera et al, 2003;Dunkley y Grilo, 2007;Sassaroli y Ruggiero, 2005), and that shrill voice is perceived usually as less secure and credible than normal voice (Rodero, 2002). In this study we have reported that AN-R patients described their voice as shrill more often than the control group (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifica los criterios para la Anorexia Nervosa (AN) (F50.0), la Bulimia Nerviosa (BN) (F.50.2), reconociendo al Trastorno por Atracón como un TCA especifico (F 50.8). Propone una lista de otros trastornos como el trastorno dismórfico muscular, el trastorno evitativo/restrictivo de la ingesta alimentaria, pica, rumiación, AN atípica, BN sub-umbral, trastorno por atracones sub-umbral, trastorno purgativo y síndrome del comer nocturno a ser mencionados en la categoría Trastorno de alimentación y de la ingestión no especificado (Behar y Arancibia, 2014).…”
Section: Descripción Del Temaunclassified